Transient absorption spectra of triplet states and charge carriers of conjugated polymers - Burrows, H. D. (2001)
The use of pulse radiolysis to study transient species in conjugated polymers in solutions is discussed, with particular reference to poly(2-methoxy-5-(2'-ethylhexoxy)-p-phenylenevinylene) (MEH-PPV). The excited triplet state is specifically generated by energy transfer on radiolysis of benzene solutions in the presence of suitable sensitisers, and its spectrum is reported. The presence of vibronic structure suggests a localised triplet state. By varying the energy of the sensitiser, it is possible to determine the energy of the lowest triplet state. Results are also presented for the triplet-triplet absorptions and energies of five other common [pi]-conjugated polymers. The MEH-PPV triplet absorption, produced on radiolysis, does not increase linearly with either polymer concentration or radiation dose. This is suggested to be due to the presence of multiple triplet excitations on the isolated polymer chains. Intrachain triplet-triplet annihilation is observed, and is seen to lead to delayed fluorescence. Spectra are also reported for the positive and negative charge carriers of MEH-PPV and the other polymers specifically produced by pulse radiolysis of the polymers in chloroform or tetrahydrofuran solutions.